PENGARUH BRAND AWARENESS DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN SEPATU FUTSAL PADA KOMUNITAS AERTEMBAGA FC - Muhamad Faisal Candra Lumiu; Yusuf Hamisi; Dhian Kenanga (LPPM Sekolah Tinggi Ilmu Ekonomi Petra Bitung, 2026)
Members of the Aertembaga FC Community show different preferences when choosing futsal shoes, both local and international brands, despite their relatively similar playing styles. This situation creates problems because product choices are no longer solely based on technical requirements, but are also influenced by brand awareness and perceived quality. This study aims to analyze the influence of brand awareness and perceived quality on futsal shoe purchasing decisions among Aertembaga FC Community members. The study used an associative quantitative approach with a total sampling technique of 48 active community members. Data were collected through a questionnaire using a Likert scale. The results showed that brand awareness significantly influenced purchasing decisions (sig. <0.001) and perceived quality also significantly influenced (sig. = 0.002). Simultaneously, both variables significantly influenced purchasing decisions (sig. F test = 0.007). The coefficient of determination (R² = 73.1%) indicates that brand awareness and perceived quality explain 73.1% of the variation in futsal shoe purchasing decisions among the Aertembaga FC Community.